(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Financial institutions are playing a vital role for economic development of the nation. Their contribution is essential one for the nation. In India both public sector banks and private financial institutions together contribute lots to the nation. So the researcher selects the topics a study on borrowers’ perception towards private financial institutions in Tirunelveli corporation area. The main aim of conducting this research is to discover the borrowers’ perception towards private financial institutions in Tirunelveli. In order to conduct this research and to achieve the objectives, the primary data has been collected by using structured questionnaire. Moreover, secondary data has been collected from published reports, journals, periodicals, newspapers, books, magazines, and other published literature. For collecting the primary data judgmental sampling method is used. To undertake this study, the sample sizes of 120 respondents were taken.